Inovasi Manajemen Kurikulum : Menyiapkan Siswa untuk Tantangan Masa Depan - Wiasti Yuana Prastiwi; Ahmad Rifai; Alfianti Syahidah Putri; Hesti Kusumaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to prepare students in the future, in order to realize students who have good competency values, a teacher has an important role in educating and preparing them. Both in terms of physical and spiritual. Technological and information advances in the future are very dangerous if a student does not get guidance in its actualization. We hope that through this article all readers can draw the conclusions that we have compiled.